Wittgenstein and ancient skepticism: disagreements, suspension of judgment and persuasion - Reinoso, Guadalupe (Estudios de Filosofía, 2019)
Recent discussions about the ancient sources of skepticism have provided new elements to evaluate the scope of the Pyrrhonian proposal and to differentiate it from modern skeptical manifestations. This, in turn, has allowed us to explore the affinities between the ideas that Sextus Empiricus exposed in his Outlines of Pyrrhonism and the ideas that Wittgenstein presented in On Certainty. My purpose is to evaluate the scope of these affnities from the place that both authors give to the problem of disagreement.